FORMULASI SEDIAAN SAMPO ANTIKETOMBE EKSTRAK DAUN ALPUKAT (Persea americana Mill) DAN UJI AKTIVITASNYA TERHADAP JAMUR Pityrosporum ovale - Mainal Furqon; Silitonga, Evawani Martalena; Br Tarigan, Frida Lina; Rini (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2021)
Avocado leaves have antifungal activity because they contain chemical compounds. This study aims to determine whether avocado leaf ethanol extract (Persea americana Mill) can be formulated info anti-dandruff shampoo preparations and determine whether avocado leaf ethanol extract ethanol has antifungal activity against pityrosporum ovale. This research is experimental in the form in the form of an organoleptic test, the results were obtained with a liquid form slightly thick with the smell of avocado extract and blackish brown in color the homogeneity test on the 4 preparations was obtained homogeneous. In the Ph test, the ph for F0 7 and FI, F2, and F3 was obtained 6. The foam heights were 11 cm, while at F2 and F2, and F3, it was 9 cm. The stabilility test. Were was no change in the preparation, and for the irritation test there was no change. Allergic to the respondent. Shampoo activity test on the four preparations obtained inhibition zones in shampoo preparations with can be concluded that avocado leaf extract shampoo has antifungal activity against the fungus pityrosporum ovale.